Ethnomedical Study of Skin Diseases (Smallpox, Measles, and Hives) in North Pringgajurang Village, District of East Lombok - Prasasthi, Winiayu Devhi; Qotrunnada, Baiq Citra Azzahra; Sasvania, Anisa; Kaori, Jasmine Zaskia; Azariani, Wiwin; Mukhlishah, Neneng Rachmalia Izzatul; Hanifa, Nisa Isneni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
In West Nusa Tenggara (NTB), infectious and allergic skin diseases occupy a significant role in the regional morbidity profile, with a relatively high number of cases. Treatment of skin diseases generally uses synthetic drugs such as antibiotics, antifungals, corticosteroids, and antihistamines. In addition to synthetic drug therapy, traditional medicine using medicinal plants can be used. Ethnomedicinal studies on skin disease treatment in East Lombok have never been conducted. People in North Pringgajurang Village, Montong Gading District, East Lombok Regency still believe in alternative medicine and use medicinal plants as traditional remedies. This study aims to determine the composition of ingredients, preparation and use methods, and the importance of certain plants for treating skin diseases by the belian in North Pringgajurang Village, Montong Gading District, East Lombok Regency. Informants were selected using the discriminatory snowball sampling method. Qualitative analysis was conducted through semi-structured interviews and quantitative analysis using the Index of Cultural Significance (ICS) for each plant species. Based on interviews with 5 informants, 12 species from 11 plant families were used to make herbal remedies for skin diseases. The herbal remedies were prepared by pounding, grinding, grating, chewing, and cutting and slicing thinly. There are 5 ways to use the herbal remedies for skin diseases: rubbing, applying, spraying, drinking, and dousing. The highest ICS score, 33, was obtained for the galangal plant (Kaempferia galanga).